Traditional Chinese exercises for postoperative rehabilitation of lung cancer patients: a network meta-analysis - Xu, Jianan; Huang, Yuerong; Liu, Ziyin; Liu, Nianshuo; Li, Cuihan; Zhang, Jianwei; Lyu, Shaojun x (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details